Processing of implicit versus explicit predictive contextual information in Parkinson's disease. (31st January 2018) - Li, Ling; Diaz-Brage, Pablo; Fernandez-Lago, Helena; Fogelson, Noa
Abstract: We investigated the effects of implicit versus explicit local contextual processing in Parkinson's disease (PD) using electrophysiological measures. EEG recording blocks consisted of targets preceded by either randomized sequences of standards or by sequences including a predictive sequence signaling the occurrence of a target event. PD patients ("on" medication) and healthy controls performed two sessions: in the first the regularity of the predictive sequence was implicit, while in the second this regularity was made explicit. PD and control subjects showed shorter reaction times for predicted versus random targets across both the implicit and explicit sessions. Healthy controls showed a facilitation of the P3b latency for predicted targets (compared with random targets) in both the implicit and explicit sessions, while PD patients showed no significant P3b latency differences between the two target conditions across both sessions. In healthy controls the P3b amplitude of the last most-informative stimulus of the predictive sequence (n-1) was larger in the explicit compared to the implicit session, while this difference was absent in PD patients. Functional connectivity measures showed that during the explicit and implicit sessions detection of n-1 was associated with higher gamma values and weaker fronto-central-parietal connections, in the theta band, in PD compared to controls. The findings suggest that implicit and explicit processing of predictive contextual information is altered in PD patients and that this may be associated with functional connectivity abnormalities within top-down frontal networks. Abstract : Highlights: Evaluation of P3b and functional connectivity using graph theory. Altered modulation of implicit versus explicit contextual processing in PD. Implicit and explicit task-dependent increase of local integration in PD. Abnormalities associated with weaker connections within frontal networks.